Phenotypically Wild Barley Shows Evidence of Introgression From Domesticated Barley - Chaochih Liu; Li Lei; Mingqin Shao; Jerome D. Franckowiak; Jacob B. Pacheco; Jeness C. Scott; Ryan T. Gavin; Joy K. Roy; Ahmad H. Sallam; Brian J. Steffenson; Peter L. Morrell (Molecular Ecology, 2026)
Multiple studies have reported genetic evidence of crop‐to‐wild introgression in phenotypically wild accessions of wild barley ( Hordeum vulgare ssp. spontaneum ). We examined 318 Wild Barley Diversity Collection (WBDC) accessions for evidence of introgression from domesticated barley. Using SNP genotyping data, we performed local ancestry inference between the WBDC accessions and domesticated barley to identify genomic regions with evidence of introgression. Using the genomic intervals for well‐characterised genes involved in domestication and improvement, we examined the evidence for introgression at genomic regions potentially important for maintaining a wild phenotype. Our analysis revealed that nearly 16% (48 of 318) of WBDC accessions showed evidence of introgression from domesticated barley, with up to 16.6% of the genome introgressed. All accessions identified as introgressed based on domestication‐related phenotypes show clear genetic evidence of introgression. The size of runs of identity by state and local ancestry inference suggests that most introgression did not occur recently. This study suggests a long history of genetic exchange between wild and domesticated barley, highlighting the potential for introgression to influence the genetic makeup and future adaptation of wild populations, with implications for plant conservation strategies.